Tuning topological and dimensional versatility from 1D to 3D of Zn/Cd luminescent biphenyl-3, 5-dicarboxylate coordination polymers by ancillary ligand. Issue 14 (17th July 2016) - Huang, Wei; Jiang, Jun; Xu, Jun; Kirillov, Alexander M.; Wu, Dayu
Abstract: The present study reports application of biphenyl-3, 5-dicarboxylic acid (H2 L ) as a versatile building block for synthesis of d 10 metal coordination polymers (CPs). Five Cd(II) and Zn(II)-containing CPs based on N, N-donor ancillary ligands, [Cd2 (μ3 -L )2 (μ2 -4, 4′-tmbpy)(MeOH)]∞ (1 ), [Cd(μ2 -L )(2, 2′-bpy)(H2 O)]∞ ·n(MeOH) (2 ), [Cd(μ2 -L )(dipt)]∞ (3 ), [Cd(μ3 -L )(phen)]∞ ·nH2 O (4 ), and [Zn(μ2 -L )(μ2 -4, 4′-tmbpy)]∞ ·nH2 O (5 ) 4, 4′-tmbpy = 4, 4′-trimethylenedipyridine, 2, 2′-bpy = 2, 2′-bipyridine, dipt = 2, 9-dimethyl-1, 10-phenanthroline, phen = 1, 10-phenanthroline have been prepared under solvothermal conditions.1 –5 have been characterized by single crystal X-ray diffraction, elemental analysis, infrared (IR) spectra, and powder X-ray diffraction (PXRD). Complex1 exhibits a three-dimensional (3-D) framework with a rarefsc-3, 4-I41/amd topology. Complexes2 –4 show one-dimensional (1-D) structures. Complex5 features a two-dimensional (2-D) layer structure with asql topology. The structural and topological diversity of1 –5 are mainly attributed to the effect of the N, N-donor ancillary ligand. Solid-state luminescent properties and thermal stabilities of the obtained products have been investigated. Abstract :